Assessment of Selected Heavy Metals and Arsenic Concentrations in Wild Boar (Sus scrofa L.) from Papuk Nature Park (Croatia) - Domagoj Vidosavljević; Miroslav Venus; Dinko Puntarić; Lidija Kalinić; Marina Vidosavljević; Mario Begović; Marta Despot; Vlatka Gvozdić (Journal of Xenobiotics)
The aim of this study was to measure the concentrations of As, Cd, Hg, Pb, Cr, Cu, Fe and Zn in the muscle, liver and kidney of wild boar (Sus scrofa) in Papuk Nature Park, Eastern Croatia. Muscles, liver and kidney of 38 wild boars, up to 3 years of age, were collected and the concentrations of elements were determined by ICP-MS. Cadmium exceeded the permitted levels acceptable for human consumption in 50% of kidney samples (max. = 6.64 mg kg−1), 20% of liver samples (max. = 4.60 mg kg−1) and 43% of muscle samples (max. = 0.672 mg kg−1). Lead exceeded acceptable levels in 63% of liver samples (max. = 0.463 mg kg−1), 51% of kidney samples (max. = 11.8 mg kg−1) and 65% of muscle samples (max. = 9.10 mg kg−1). Mercury concentrations in the liver were higher than allowed in 13% (max. = 0.552 mg kg−1) in kidneys in 27% (max. = 0.484 mg kg−1), and in the muscles in 15% (max. = 0.103 mg kg−1) of cases. Arsenic concentrations in muscles exceeded the permissible value in 30% of cases (max. = 0.286 mg kg−1). The concentrations of Cr, Cu, Fe and Zn did not significantly differ from the values reported in other studies. Median concentrations of Cr, Cu, Fe and Zn ranged as follows: muscle (0.193, 2.94, 44.5 and 20.6 mg kg−1), kidney (0.140, 5.32, 110 and 23.3 mg kg−1) and liver (0.130, 3.71, 278 and 36.0 mg kg−1).